Digital Humanities and the Discontents of Meaning. Issue 2 (July 2020) - Fuller, Michael A.
Abstract : The digital humanities offer more than just a set of tools. The application of software to assist in the analysis of large collections of data does not just expand the volume of material we can incorporate in our work, it also expands how we in the humanities understand the nature of meaning. The recent scholarly turn to the expanded modes of analysis made possible by DH is not just the "latest new thing" but gives the scholarly community a way to articulate and respond to long-standing doubts about the epistemological grounding in the practice of the humanities. Even more importantly, I believe that this broadening of inquiry afforded by DH is intrinsic to the humanistic project itself. In this essay, I seek in particular to connect the implicit conceptual substructure behind the architectural logic of the digital humanities to key strains of hermeneutic thought that have established a basis for exploring the question of how we are to understand the vast, variegated world of historical human experience that is the object of our humanistic inquiries across disciplines.